Relationship between Work-Related Quality of Life and Job Satisfaction in Iranian Occupational Therapists - Hamid Reza Rostami; Malahat Akbarfahimi; Amin Ghaffari; Mohammad Kamali; Mehdi Rassafiani (Occupational Therapy International)
Objective. This study is aimed at exploring the relationship between the work-related quality of life and job satisfaction among Iranian occupational therapists. Methods. In an analytical-descriptive, cross-sectional study, 322 occupational therapists were recruited through a convenient sampling. Inclusion criteria consisted of age between 22 and 50 years, at least one-year work experience, 24 hours of working per week as an occupational therapist, and membership of Iranian Occupation Therapy Association. After signing the informed consent and completing demographic information, each participant completed the Minnesota Satisfaction Questionnaire- Short Form (MSQ-SF) and work-related quality of life scale. Results. The highest quality of working life belonged to occupational therapists who were female, married, with an annual salary of more than 40000$ (compared to below 20000 $), and those with work experience between 5 and 12 years. There was a positive and significant relationship between work-related quality of life and job satisfaction. Work-related quality of life scores could significantly predict MSQ-SF scores (β1=0.54, p<.001). Conclusions. The significantly positive relationship between work-related quality of life and job satisfaction suggests the importance of organizational programs for enhancing factors of work-related quality of life in order to improve job satisfaction and quality of life among Iranian occupational therapists.